Spin-orbit coupling and the topology of gases of spin-degenerate cold excitons in photoexcited GaAs-AlGaAs quantum wells - Matuszewski, M. (2017)
We calculate the spatial structure of four-component spinor systems of mixed bright and dark exciton condensates in coupled quantum wells. The spin-dependent bright-dark exciton conversion and Dresselhaus spin-orbit coupling is found to generate a rich variety of topological elements. By propagating the Gross-Pitaevskii equation in imaginary time, we observe the following: single and multiple polarized vortices; the phase separation of bright and dark excitons; and exotic spatial structures in density and spin polarization.